AKSESIBILITAS PEMILIHAN KEPALA DAERAH SERENTAK BAGI WARGA NEGARA DISABILITAS - Fajri Nursyamsi; Estu Dyah Arifianty (Magister Ilmu Politik Universitas Hasanuddin, 2016)
Persons with disabilities are part of Indonesian citizen, thus entitled to the respect, protection and fulfillment of basic rights guaranteed in the Constitution NRI 1945. One of the fundamental rights which are owned by a citizen is to participate in the elections, including local elections, to use their right to vote. However, fulfillment of the right to vote which is had by persons with disabilities is often neglected. Regulation becomes the most fundamental cause in the practice of discrimination against persons with disabilities to use their right to vote. In the process of legislative and presidential election in 2014, the regulatory aspects became an attention, so it continues to be refined through the implementation of the regulations established by the General Election Commission (KPU). But the effort was apparently not done systematically, as in Law Number 8 Year 2015 on the Enactment of Government Regulation in Lieu of Law No. 1 Year 2014 on the Election of Governor, Regent, and Mayor. There are provisions in those regulation that discriminate persons with disabilities in certain varieties. The provision in question is Article 57 paragraph (3) states,